2010
DOI: 10.3109/10837450.2010.531734
|View full text |Cite
|
Sign up to set email alerts
|

Study of the influence of alkalizing components on matrix pellets prepared by extrusion/spheronization

Abstract: The aim of this study was to investigate the effects of alkalizing components and the nature of the wetting liquid on the properties of matrix pellets prepared by extrusion and spheronization. Atenolol was used as an active pharmaceutical ingredient, ethylcellulose as a matrix former, microcrystalline cellulose as a filler and disodium phosphate anhydrous and trisodium phosphate dodecahydrate as alkalizing materials. Water and a water-ethanol mixture served as granulation liquids. Pellet formation was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In order to obtain a very good mass for this process, it is necessary to use MCC and the matrix former together. Ethylcellulose (EC) has frequently been used as a coating material for tablets and pellets (Wallace, 1990;Iyer et al, 1993;Ye et al, 2007) and as a binder in the preparation of microcapsules and microspheres, but it is also used as a monolithic matrix former for formulations in which modified drug release is ensured by diffusion (Corti et al, 2008;Huang et al, 2006;Fan et al, 2001). Several commercially available polymers are suitable for the coating of pharmaceutical dosage forms (McGinity, 1997), and some can be used to control the drug release kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a very good mass for this process, it is necessary to use MCC and the matrix former together. Ethylcellulose (EC) has frequently been used as a coating material for tablets and pellets (Wallace, 1990;Iyer et al, 1993;Ye et al, 2007) and as a binder in the preparation of microcapsules and microspheres, but it is also used as a monolithic matrix former for formulations in which modified drug release is ensured by diffusion (Corti et al, 2008;Huang et al, 2006;Fan et al, 2001). Several commercially available polymers are suitable for the coating of pharmaceutical dosage forms (McGinity, 1997), and some can be used to control the drug release kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of a multiparticulate matrix system with an alkalizing component is a reasonable way to ensure an appropriately alkaline micromilieu (Hamedelniel et al, 2010a). Trisodium phosphate dodecahydrate was incorporated as alkalizing and pore-former substance; our previous work had revealed that a matrix-former polymer is required to control the parallel release of At and the alkalizing component utilized (Hamedelniel et al, 2010b) and to ensure that the dosage form reaches the intestine in intact form. Thus, it is necessary to prepare a delayed-release product.…”
Section: Declaration Of Interestmentioning
confidence: 99%